Young witnesses of intimate partner violence: screening and intervention. Issue 1 (1st January 2019) - Rydström, Lise-Lott; Edhborg, Maigun; Ring Jakobsson, Lisa; Kabir, Zarina Nahar
ABSTRACT: Intimate partner violence is a public health problem worldwide. Many children witness intimate partner violence at home and are affected by it. Regardless of the degree of exposure, children growing up in violent homes experience negative effects in the form of externalising behaviour and internalising symptoms which call for targeted interventions for children. The aim of the study is to map i) the available methods of detecting child and adolescent witnesses of intimate partner violence and ii) the interventions to support them. Three databases, PubMed, PsychInfo and Social Services Abstracts, were searched for scientific publications spanning over 20 years (1997–2017). This resulted in 2, 406 publications of which 15 were finally selected after screening. Analysis of the articles resulted in three categories. The process of detecting children and adolescents who witnessed IPV in their homes varied in the included studies. The children were most commonly identified through their mother or other caregivers. Very few studies were based on children's own reporting of their experiences, but were rather based on the mothers' proxy reports. Studies distinguishing between the different forms of violence witnessed by children were few. It was uncommon that children were directly identified or screened for witnessing IPV in the family.